PENGARUH ENTREPRENEURIAL MARKETING TERHADAP PENINGKATAN COMPETITIVE ADVANTAGE UMKM - Hasanah, Nabilatul; Jannah, Miftahul (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to analyze the effect of implementing the seven dimensions of entrepreneurial marketing on increasing the competitive advantage of MSMEs in Sampang Regency. This quantitative research uses a purposive sampling technique, and the sample size collected was 155 MSMEs. The results of this study revealed that four dimensions of entrepreneurial marketing—customer intensity, innovativeness, resource leveraging, and value creation—partially have a significant effect on competitive advantage. While proactiveness, opportunity focus, and calculated risk-taking partially have no significant effect on competitive advantage. However, simultaneously, the seven dimensions of entrepreneurial marketing have a significant effect on the competitive advantage of MSMEs in Sampang Regency. This research is limited to Sampang Regency, so the results may not be generalizable to other regions. Therefore, further research is recommended to involve a larger and more diverse sample, such as MSMEs throughout Madura, and consider using different dimensions of the entrepreneurial marketing concept as variables. Keywords: Entrepreneurial Marketing; Competitive Advantage; MSME